Innovation In Islamic Religious Education Learning: A Study Of The Implementation Of Digital Citizenship In The Adab Mentoring Program - Muharromah, Fityatul; Anshory, Isa (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
This study aims to analyse the implementation of an adab mentoring program that integrates digital citizenship values and its impact on student character development at Al Abidin Bilingual Boarding School, Surakarta. The study employed a qualitative approach, utilising a case study method, with informants comprising Islamic Religious Education teachers, program coordinators, mentors, and students. Data were collected through observation, semi-structured interviews, and school documentation. The results indicate that the adab mentoring program successfully linked Islamic adab values with digital citizenship principles, including digital communication ethics, tabayyun (religious conduct), digital amanah (trustworthiness), and Islamic leadership. Implementation was carried out through routine activities, discussions, case studies, and reflections on students' digital experiences, supported by a boarding school environment that facilitates habituation and intensive supervision. The program's impact is evident in students' more polite behaviour, critical information filtering, disciplined use of devices, and emulating Islamic leadership digitally. This program effectively forms an Islamic character that is adaptive to the challenges of the digital era.